SARS-CoV-2 excretion kinetics in nasopharyngeal and stool samples from the pediatric population - Khemiri, Haifa; Gdoura, Mariem; Ben Halima, Samar; Krichen, Henda; Cammà, Cesare; Lorusso, Alessio; Ancora, Massimo; Di Pasquale, Adriano; Cherni, Asma; Touzi, Henda; Sadraoui, Amel; Meddeb, Zina; et al. (Frontiers in Medicine, 2023)
Background The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for serious respiratory infections in humans. Even in the absence of respiratory symptoms, gastrointestinal (GI) signs were commonly reported in adults and children. Thus, oral–fecal transmission was suspected as a possible route of infection. The objective of this study was to describe RNA shedding in nasopharyngeal and stool samples obtained from asymptomatic and symptomatic children and to investigate virus viability. Methods This study included 179 stool and 191 nasopharyngeal samples obtained from 71 children, which included symptomatic (n = 64) and asymptomatic (n = 7) ones. They were collected every 7 days from the onset of the infection until negativation. Viral RNA was detected by real-time RT-PCR, targeting the N and ORF1 genes. Whole-genome sequencing was performed for positive cases. Viral isolation was assessed on Vero cells, followed by molecular detection confirmation. Results All cases included in this study (n = 71) were positive in their nasopharyngeal samples. SARS-CoV-2 RNA was detected in 36 stool samples obtained from 15 out of 71 (21.1%) children; 13 were symptomatic and two were asymptomatic. Excretion periods varied from 7 to 21 days and 7 to 14 days in nasopharyngeal and fecal samples, respectively. Four variants were detected: Alpha (n = 3), B.1.160 (n = 3), Delta (n = 7), and Omicron (n = 1). Inoculation of stool samples on cell culture showed no specific cytopathic effect. All cell culture supernatants were negative for RT-qPCR. Conclusion Our study demonstrated nasopharyngeal and fecal shedding of SARS-CoV-2 RNA by children up to 21 and 14 days, respectively. Fecal shedding was recorded in symptomatic and asymptomatic children. Nevertheless, SARS-CoV-2 was not isolated from positive stool samples.